Feasibility of a commercial smartphone application for dietary assessment in epidemiological research and comparison with 24-h dietary recalls - Ambrosini, G.; Hurworth, M.; Giglia, Roslyn; Trapp, G.; Strauss, P. (2018)
© 2018 The Author(s). Background: Dietary assessment methods that can provide high quality data while limiting participant burden and resource requirements in epidemiological research are highly sought after and continue to evolve. The use of mobile phone technology in research has increased rapidly over the last decade and offers multiple advantages to the researcher over traditional data collection methods. This study tested the acceptability and relative validity of a commercial smart phone application (app) for use as an epidemiological dietary assessment tool, compared with a traditional dietary assessment method. Methods: Study participants completed a 4-d food diary using a modified version of the Easy Diet Diary app and two 24-h dietary recalls during the same week, for comparison. At the end of data collection, participants completed a questionnaire on their experience with both methods. Average proportions of energy from macronutrients and fibre, iron, and calcium densities from the app and 24-h recalls were compared after log transformation, by calculating mean agreement, limits of agreement (LOA), and Pearson's correlations. The prevalence of dietary under-reporting was compared in each method using the Goldberg method. Results: A total of 50 adults (82% women) provided data for analysis (mean age, 31 y; mean BMI, 22.4 kg/m 2 ; 14% overweight or obese). Participant feedback showed high levels of acceptance of the app; 83% preferred using the app to completing 24-h dietary recalls. The average difference in energy intake (mean agreement) between methods was 268 kJ/d. For all intakes except alcohol, the average difference between methods was not significantly different from zero. Most limits of agreement were within an acceptable range. The prevalence of dietary misreporting was similar in both methods. Conclusions: These findings demonstrate good feasibility for applying this commercially-developed smartphone app in epidemiological research.